Estudo comparativo do desgaste de corpos de prova em um tribômetro reichert test - Yamashita, Roberta Cristine (2018)
As the demand for lower cost and environmental impact products increase, many companies have been enhancing their number of researches and revaluing their processes. In fact, studies have shown different alternatives that decreases the final cost of the product without altering the quality, also preserving the environment. In these cases, the technological progresses have been helping. As an alternative, industries have been investing in fluids of vegetable base due to these fluids cause less environmental impact, and they have lower cost. The focus of this work is to compare the wear between a pair of standardized sample and a pair of generic sample. The standardized sample is imported and it has a high purchase cost, therefore it is necessary to study the availability of using generic samples for further analyzes. For a start, the pin was measured for standardized material, then, the ABNT 1020 was chosen as a material for the generic pin and for the bearing for the generic ring. Furthermore, the temperature sensors were adapted in a Reichert Test machine, which is wear test. The function of the Reichert Test machine is to provide friction and wear tests under controlled conditions, where the tests were performed using Jatropha oil in nature as the lubricating fluid. Tribological tests give information about the lubricity of the used fluid. Then, using pre-determined parameters, the wear of which sample was measured. The results using the Reichert Test and tribological tests were satisfactory, constants and stables. Moreover, the results using generic samples showed moderate wear when compared to the results for the standardized sample. In conclusion, these results have shown the possibility of use generic samples as an alternative for standardized samples in tests of wear using tribometer of Reichert Test type.